2023
DOI: 10.1177/25158414231197072
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immuno-inflammatory index in patients with pseudoexfoliation syndrome and pseudoexfoliative glaucoma

Nejla Tukenmez Dikmen,
Yasemin Un

Abstract: Background: In recent years, the role of some hematological parameters used as chronic inflammation markers in the pathogenesis of many ocular and systemic diseases has been investigated. For ocular diseases such as uveitis, keratoconus, and retinal vein occlusion, the neutrophil/lymphocyte ratio (NLR) and systemic immune-inflammatory index (SII) have been reported to be useful inflammatory biomarkers. It has also been reported that low-grade chronic inflammation plays a role in the formation of pseudoexfoliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Among PEX-related in ammatory index studies, Ozgonul et al detected that NLR and PLR were high in PEX patients and that a high NLR could predict PEXS and PEXG [12]. In the study of Tukenmez Dikmen et al, it was stated that the PEXS group had the highest NLR and SII values, followed by the PEXG and control groups, and there was no difference in PLR values between the groups [14]. In another study, Mirza et al compared the monocyte count/high-density lipoprotein ratio (MHR) and lymphocyte/monocyte ratio (LMR) indexes in PEX and control groups, and detected that MHR was higher and LMR was lower in the PEX group than the healthy group [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among PEX-related in ammatory index studies, Ozgonul et al detected that NLR and PLR were high in PEX patients and that a high NLR could predict PEXS and PEXG [12]. In the study of Tukenmez Dikmen et al, it was stated that the PEXS group had the highest NLR and SII values, followed by the PEXG and control groups, and there was no difference in PLR values between the groups [14]. In another study, Mirza et al compared the monocyte count/high-density lipoprotein ratio (MHR) and lymphocyte/monocyte ratio (LMR) indexes in PEX and control groups, and detected that MHR was higher and LMR was lower in the PEX group than the healthy group [21].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophillymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in ammatory indexes were observed to be signi cantly higher in PEXS and PEXG patients than healthy group [12]. In a study evaluating another in ammatory index marker, the systemic immuno-in ammatory index (SII), it was found that there was an association between higher SII with PEXS and PEXG [14]. These studies suggested that PLR, NLR, and SII may be useful in predicting the prognosis of PEXS patients and progression to PEXG.…”
Section: Introductionmentioning
confidence: 99%